Optical sensor based on dye-sensitized solar cell with tobacco chlorophyll - Eka Maulana; Rahmadwati Rahmadwati; Sapriesty Nainy Sari; Akhmad Sabarudin (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
Modified optical sensor based on dye-sensittized solar cell has been successfully fabricated to measure the number of light energy. The electric parameters as the sensor output were achieved from the light illuminance as the sensor input. The measured parameter from optical sensor according to the voltage and current output have been characterized to obtain the sensor performance. In this research, the modified sensor is customized from dye-sensitized solar cell with extracted tobacco chlorophyll dye as the photo-catalysator, photo-electrode of titanium dioxide and Iodine solution for redox reaction. The thick layer deposition with selected material is conducted using spin coating method of 1000 rpm. Based on the absorbance measurement, it shows that tobacco dye has the characteristics of visible light absorption in the wavelength of visible light spectra. The analytical result shows that the sensor has the wide linear characteristic in certain light illuminance and the increasing light intensity produces higher electrical parameter output both current and voltage. This sensor has potential prospect to be used as a light sensor and to be competitive fabrication cost.